Distinguishing Relational Aspects of Character Strengths with Subjective and Psychological Well-being - Hausler, Melanie; Strecker, Cornelia; Huber, Alexandra; Brenner, Mirjam; Höge, Thomas; Höfer, Stefan (Frontiers in Psychology, 2017)
Research has shown that character strengths are positively linked with well-being in general. However, there has not been a fine-grained analysis up to date. This study examines the individual relational aspects between the 24 character strengths, subjective well-being (SWB), and different aspects of psychological well-being (PWB) at two times of measurement (N = 117). Results showed that overall the “good character” was significantly stronger related with PWB than with SWB. The character strength “hope” was at least moderately correlated with the PWB aspects meaning, optimism and autonomy, and “zest” with the PWB aspects relationships and engagement. “Persistence” showed the highest correlation with the PWB aspect mastery. Out of the 24 character strengths, the happiness-related strengths (hope, zest, gratitude, curiosity, and love) were more likely to correlate with PWB and SWB than any other character strength. This study offers a more fine-grained and thorough understanding of specific relational aspects between the 24 character strengths and a broad range of well-being aspects. Future studies should take up a detailed strategy when exploring relationships between character strengths and well-being.